THE ANALYSIS ON STUDENTS’ TRANSLATION METHOD IN LABEL PRODUCT - Widianingsi Ramlan (LP2M IAIN Sultan Amai Gorontalo, 2017)
The aimed of this research were to analyze the translations method in translating label product that used by the student at eight semester English Department and to find out the dominant method that used in translating label product by the students at the eight semester English Department in IAIN Sultan Amai Gorontalo those should be the reference material in evaluating and teaching English subject. This research used qualitative method by technique of collecting the data such as student’s worksheet and documentations. In the technique the analyzing the data, the researcher does the steps that is reading, classifying, explaining, and drawing conclusion. The translation methods that classifying that is word-for-word translation, literal translation, faithful translation, semantic translation, adaptation translation, free translation, idiomatic translation, communicative translation, pragmatic translation, dynamic translation, esthetic-poetic translation, and linguistic translation. The result of research showed of the methods that used in student’ translation in label product are word-for-word translation is 13 sentences, literal translation is 24 sentences, free translation is 29 sentences, pragmatic translation is 6 sentences, and idiomatic translation is 5 sentences. Thus, the dominant method that used in student’s translation is free translation by 29 sentences.